Baroreflex control of lumbar and renal sympathetic nerve activity in conscious rats - Kanbar, Roy (2008)
This study compared the baroreflex control of lumbar and renal sympathetic nerve activity (SNA) in conscious rats. Arterial pressure (AP) and lumbar and renal SNA were simultaneously recorded in six freely behaving rats. Pharmacological estimates of lumbar and renal sympathetic baroreflex sensitivity (BRS) were obtained by means of the sequential intravenous administration of sodium nitroprusside and phenylephrine. Sympathetic BRS was significantly (P < 0.05) lower for lumbar [3.0 ± 0.4 normalized units (NU)/mmHg] than for renal (7.6 ± 0.6 NU/mmHg) SNA. During a 219-min baseline period, spontaneous lumbar and renal BRS were continuously assessed by computing the gain of the transfer function relating AP and SNA at heart rate frequency over consecutive 61.4-s periods. The transfer gain was considered only when coherence between AP and SNA significantly differed from zero, which was verified in 99 ± 1 and 96 ± 3% of cases for lumbar and renal SNA, respectively. When averaged over the entire baseline period, spontaneous BRS was significantly (P < 0.05) lower for lumbar (1.3 ± 0.2 NU/mmHg) than for renal (2.3 ± 0.3 NU/mmHg) SNA. For both SNAs, spontaneous BRS showed marked fluctuations (variation coefficients were 26 ± 2 and 28 ± 2% for lumbar and renal SNA, respectively). These fluctuations were positively correlated in five of six rats (R = 0.44 ± 0.06; n = 204 ± 8; P < 0.0001). We conclude that in conscious rats, the baroreflex control of lumbar and renal SNA shows quantitative differences but is modulated in a mostly coordinated way.